Pneumatosis intestinalis after thoracic organ transplantation in children: A case series and review of the literature. Issue 6 (3rd April 2022) - Atwood, Daniel; Nelson, Amanda; Rosen, Rachel; Esteso, Paul; Visner, Gary; Midyat, Levent
Abstract: Pneumatosis intestinalis (PI) is a rare complication after thoracic organ transplantation. There are several theories for explaining the pathophysiology of this disease. In this paper, we highlight three cases of PI in a single pediatric center, one after lung transplantation and two after heart transplantation. Although the presentations differed, all cases improved with non‐surgical therapies. There are not many articles in the pediatric literature about post‐transplantation PI, and there are still many questions regarding the incidence, etiology, and treatment for this disease.